Invitation for meeting regarding lockdown for a week from 5th April, 2021 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding invitation for meeting of BRAC University new campus project regarding lockdown for a week from 5th April, 2021.